QUARDRANGLE BOTTOM LINE (QBL) DALAM PRAKTIK SUSTAINABILITY REPORTING DIMENSI “SPIRITUAL PERFORMANCE” - Muhammad Suyudi (Jurnal Akuntansi Multiparadigma, 2012)
Abstract:  Quardrangle Bottom Line (QBL) in “Spiritual Performance” Sustainability Reporting Practice Dimension. Business organization as an entity has a main priority to obtain profit. Economic aspect is regarded more dominant than social and environmental aspects, and will result in ecology balance disturbance or “Environmental Crisis”. The purpose of this research is to identify various phenomenon in a business entity to present ‘Sustainability Reporting’ as an essential need. Phenomenology is used in this research. The results of this research can be presented as Quadrangle Bottom Line Concept where economic performance, social and environmental performance will not be achieved if spiritual performance dimension has not yet been caught. Abstrak:  Quardrangle Bottom Line (QBL) dalam Praktik Sustainability Reporting Dimensi “Spiritual Performance”. Organisasi bisnis sebagai suatu entitas memiliki tujuan utama mendapatkan laba.  Aspek ekonomi dipandang lebih dominan daripada aspek-aspek sosial dan lingkungan dan ini menyebabkan gangguan ekologis atau “Krisis Lingkungan”. Tujuan riset ini adalah untuk mengindentifikasi berbagai fenomena dalam entitas bisnis untuk menyajikan “Sustainability Reporting” sebagai kebutuhan yang penting.  Paradigma interpretif-fenomenologi digunakan dalam riset ini.  Hasil riset dapat disajikan sebagai Quadrangle Bottom Line Concept di mana kinerja ekonomi, sosial dan lingkungan tidak akan dapat dicapai apabila kinerja spiritual tidak tercapai.